Beyond The Classroom: Linking TVET Educators’ Knowledge and Skills for Industry 4.0 Readiness - Hashim, Suhaizal (Online Journal for TVET Practitioners, 2024)
The integration of modern technologies such as artificial intelligence and the Internet of Things (IoT) is causing a significant transformation in the education sector during the Industrial Revolution 4.0 (IR 4.0). Education is increasingly focused on fostering digital literacy and creativity to equip students with the necessary abilities to confront future issues. However, educators in Malaysia continue to encounter difficulties in comprehending and implementing the principles of Industrial Revolution 4.0 within their instructional environment. The primary impediment to instructors properly incorporating technology in teaching and learning is the absence of exposure and training opportunities specifically focused on technology 4.0. Thus, this study aimed to determine the proficiency of Technical and Vocational Education and Training (TVET) educators in terms of their knowledge and skills throughout the era of IR 4.0. This study included a total of 135 participants from three TVET institution in the state of Johor, Malaysia. The study utilised a quantitative methodology to collect conclusive and unambiguous evidence for statistical analysis through the use of a questionnaire. The study’s findings indicate that most of the TVET educators possess a high level of preparedness in terms of knowledge (M=4.05) and skills (M=4.13) throughout the era of IR 4.0. The findings indicate a significant correlation between the proficiency of TVET teachers in the context of the IR 4.0, with a correlation coefficient of 0.46 (p < .001). This suggests that as these teachers become more proficient, IR 4.0 technologies are more successfully integrated into educational processes. Well-equipped educators are crucial in educating pupils for a digitally advanced workforce. Policymakers and educational institutions should invest in technical and vocational teacher professional development programmes to improve their skills and stay current with technology, creating a more effective and future-ready educational system